All Rhodes lead here : a novel - Zapata, Mariana (Avon Books, an imprint of HarperCollinsPublishers, 2024)
"Aurora De La Torre, or Ora to her friends, knows moving back to Pagosa Springs, Colorado...isn't going to be easy...But after breaking up with her longtime, famous musician boyfriend, hiding out in a small town in the mountains might be the perfect remedy for a broken heart. And checking out her landlord...might cure it, too...Fiercely protective of his family and distrusting of strangers, gruff and grumpy Rhodes initially keeps little miss sunshine Ora at a distance. But over days and weeks, long hikes and fireside chats, Aurora breaks down his walls"--